The Influence of Differentiation Strategy, Market Adaptation, and Digital Capability on Competitive Advantage: The Mediating Role of Business Agility in E-Commerce Firms - Suryani, Umi; Dwiputra, Irsyad Parama (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Differentiation Strategy, Market Adaptation, and Digital Capability on Competitive Advantage, with Business Agility serving as a mediating variable in e-commerce companies in Indonesia. A quantitative approach was employed using a causal research design. Data analysis was conducted through Structural Equation Modeling-Partial Least Squares (SEM-PLS), as it effectively handles complex models and small to medium-sized samples. Data were collected via an online questionnaire distributed to business managers, digital strategists, and decision-makers in e-commerce firms. A total of 110 respondents were analyzed using a purposive sampling technique. The results indicate that both Differentiation Strategy and Digital Capability have a significant effect on Competitive Advantage, both directly and indirectly through Business Agility. Meanwhile, Market Adaptation only has a significant indirect effect through Business Agility. These findings highlight that Business Agility plays a crucial mediating role in strengthening competitive advantage in the digital era.